2002
DOI: 10.1002/ar.10179
|View full text |Cite
|
Sign up to set email alerts
|

Polarized light microscopic analyses of collagen fibers in the rat incisor periodontal ligament in relation to areas, regions, and ages

Abstract: We prepared decalcified sagittal sections (20 m thick) from the incisal, middle, and basal regions of the mandibular incisor of male Wistar rats aged 2, 6, 12, and 24 months, and examined the sections using polarized light microscopy. Most of the birefringent fibers appeared to run obliquely across the periodontal ligament. Birefringent fibers running parallel to the long axis of the incisor were also found in the intermediate area of the ligament. Similar fiber architecture was observed in all four age groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…PLM has been proven effective to characterize collagen of tendons [20,21], ligaments [22] and other soft tissues [23]. The possibility of using PLM in the cornea was discussed almost two decades ago for ex-vivo tissues [24], and more recently to study the cornea stroma in vivo [25].…”
Section: Introductionmentioning
confidence: 99%
“…PLM has been proven effective to characterize collagen of tendons [20,21], ligaments [22] and other soft tissues [23]. The possibility of using PLM in the cornea was discussed almost two decades ago for ex-vivo tissues [24], and more recently to study the cornea stroma in vivo [25].…”
Section: Introductionmentioning
confidence: 99%
“…The results herein described are in line with the observations by Chiba et al (1990) and Komatsu et al (1998), that the mechanical properties of the periodontal ligament of continuously erupting incisors increase in incisal direction. It was also shown in rat incisors that the molecular organization of periodontal ligament collagen fibers increases from basal to incisal (Komatsu et al, 2002).…”
Section: Discussionmentioning
confidence: 88%
“…4) treated only with EMD, EMD was intensively adhered to the root surface in the form of granules of various sizes in accordance with the arrangement of collagen fibers. The direction of collagen fibers may have an affect on periodontal tissue resistance due to affecting the adhesiveness to root surface (22,34). Zhou et al (42) reported nicotine and P. gingivalis had an additive effect on human gingival fibroblast-mediated collagen degradation and these findings help to explain why smoking is a major factor contributing to the initiation and/or exacerbation of periodontal diseases.…”
Section: Resultsmentioning
confidence: 99%